Just joking 4 : 300 hilarious jokes about everything, including tongue twisters, riddles, and more! - Pattison, Rosie Gowsell (Washington, D.C. : National Geographic, 2013)
Presents a variety of jokes and facts, including knock-knocks, tongue twisters, riddles, and traditional question and answer jokes.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Description based on print version record.
Keywords: Wit and humor, Juvenile; Wit and humor; Jokes; Electronic books- OSLIS; Wit and humor, Juvenile; Humor; Tongue twisters; Knock-knock jokes; Trivia and miscellanea; Riddles; Electronic books